PENETAPAN KADAR ASAM LEMAK BEBAS DAN BILANGAN PEROKSIDA PADA MINYAK GORENG YANG DIGUNAKAN PEDAGANG GORENGAN DI JL. A.W SJAHRANIE SAMARINDA - Henny Nurhasnawati (Jurnal Ilmiah Manuntung, 2015)
Free fatty acids and peroxide are part of cooking oil quality parameters. This study aims to determine the levels of free fatty acids and peroxide value in cooking oil used by fried merchant in Jl. A.W. Sjahranie Samarinda. Sampling was done by total sampling which is cooking oil before frying and after frying a few times from four fried merchants. Determination of free fatty acid content using alkalimetry method and levels of peroxide using iodometric method.The test results of the free fatty acid content of samples A, B, C, D cooking oil before frying is equal to 0.16%; 0.27%; 0.33%; 0.32%, and free fatty acid levels after few times frying is 0.19%; 0.29%; 0.37%; 0.36%. The test results of the peroxide sample A, B, C, D cooking oil before frying in the amount of 18.95 meq O2/kg; 27.63 meqO2/kg; 24.67 meq O2/kg; 23.29 meq O2/kg. Peroxide levels after several times frying is 26.25 meqO2/kg; 35.72 meqO2/kg; 34.54 meqO2/kg; 33.16 meqO2/kg. Average levels of free fatty acids cooking oil before frying is 0.27% and after frying to 0.30%, or an increase of 12.04%. While the average level of peroxide cooking oil before frying of 23.64 meqO2/kg and after frying be 32.42 meqO2/kg or an increase of 37.16%.